Pelatihan Pengolahan Limbah Gedebog Pisang menjadi Keripik sebagai Produk Ramah Lingkungan - Azizah, Yuliatin; Amin, Saiful; Maspufah, Hayatul; Supeni, Nely (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The Andongsari Village Community, Ambulu District, is a banana-producing area and has banana stem waste. This waste can be used as a green product that can help community welfare. The purpose of this community service is to optimize waste that can be processed into Banana Stem Chips as a green product. The community service method begins with observations of the potential of the village and places that produce banana stem waste, then the method of counseling and socialization to the community through PKK mothers' activities. Furthermore, business management training and how to make products with banana stems were held with an emphasis on digital marketing. The success of the community's production is a starting point for the follow-up plan for this assistance, namely brand training, promotion, and advertising so that the new product can optimally generate income for the mothers of the Andongsari Village community, Ambulu District.